PEMBELAJARAN MENULIS KARANGAN DESKRIPSI DENGAN MODEL KOOPERATIF TIPE STAD TERHADAP SISWA KELAS X MAN 3 ACEH UTARA - Istiqamah Istiqamah (Jurnal Ilmiah Didaktika, 2019)
The aim of the study was to determine the influence of the application of learning descriptive writing by using cooperative model of Student Teams Achievement Division (STAD) type. The research method used was experimental method, with a quasi-experimental design. This research was limited to the third year of class X students of MAN 3 in North Aceh District, while the sample of the study was the students of social class X2. The data analysis used in this study was t-test analysis by the Paired Samples T-Test model. As a result, the study showed that learning descriptive writing by using STAD type of cooperative model went well and provided better learning outcomes. It is proven by the average value of pre-test and post-test results. The results of pre-test test obtained an average value was 70.21, while the results of the post-test test obtained an average value was 87.79. Thus, there was a split about 17.58 between the results of pre-test and post-test. The Paired Sample t-test results showed significance of sig-0.00. This was less than a significant level of 0.05, meaning that H0 was rejected and Hi was accepted, and there was a positive influence on the application of learning descriptive writing by using STAD type of cooperative model.